2018
DOI: 10.13187/ejced.2018.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Demographic, Academic Characteristics and Performance in Registered General Nursing Licensing Examination in Ghana

Abstract: The decreasing performance of student nurses in the professional licensure examinations (LE) in Ghana is a major concern to stakeholders, especially at a time when the nurse-patient ratio stands at 1: 1500. The study sought to determine the effect of students' demographic and academic characteristics on performance in the Registered General Nursing (RGN) LE. A descriptive retrospective study was conducted using a researcher designed checklist to review the administrative and academic records of 324 nursing stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In a related study in the United States of America, Mitchell 15 , discovered that a combination of nursing program academic outcomes predicted NCLEX-RN performance. Similarly, Doe et al 16 in their study found that performance in the licensure examinations seemed to increase with an increase in Final Grade Point Average (FGPA). There was a positive relationship between the final grade point of students and licensure examinations outcome at a 0.05 confidence level.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…In a related study in the United States of America, Mitchell 15 , discovered that a combination of nursing program academic outcomes predicted NCLEX-RN performance. Similarly, Doe et al 16 in their study found that performance in the licensure examinations seemed to increase with an increase in Final Grade Point Average (FGPA). There was a positive relationship between the final grade point of students and licensure examinations outcome at a 0.05 confidence level.…”
Section: Discussionmentioning
confidence: 77%
“…In a related study, Truman discovered that students who passed the National Council Licensure Examination-Registered Nurse (NCLEX-RN) possessed statistically higher pre-admission Grade-Point Average (GPAs) (p=0.011) and Scholastic Aptitude Test (SAT) verbal scores (p=0.009), than those who failed 13 . Similarly, Doe et al, 16 established an association between entry grades obtained in the West African Senior School Certificate Examination (WASSCE) and performance in the licensure examinations. It was discovered that 45.5 % of students with an entry aggregate between 20 and 24 failed licensure examinations, while the majority (76.9%) with an entry aggregate of 11-14 passed the examinations on the first sitting.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations